Environmental implications and evidence of natural products from dental calculi of a Neolithic–Chalcolithic community (central Italy) - Alessia D’Agostino (Nature Portfolio, 2021)
Abstract In this contribution, we investigated the role of plants in the prehistoric community of Casale del Dolce (Anagni, FR, central Italy), through microparticles recovered from dental calculus. The finding of a great amount of pollen types, even in form of compact lumps, could indicate use of natural substances, such as honeybee products and/or conifer resins. This plant-microremain record also suggested environmental implications relative to the Neolithic and Chalcolithic period. Additionally, the stability of the tartar microenvironment had preserved starches and other microparticles, such as one epidermal trichome, a sporangium, and fragments of plant tissue, rarely detected in ancient dental calculus. The detection of secondary metabolites in the ancient matrix confirmed the familiarity of this community with plant resources. All these data supply various interesting food for thought and expand the knowledge about the potential of dental calculus in archaeological and archaeobotanical fields with a special focus on palaeoecology.